Predicting the Patriarchal Politics of Pandemics From Mary Shelley to COVID-19 - Botting, Eileen Hunt (Frontiers in Sociology, 2021)
I examine the predictive powers of the political science fictions of Mary Shelley, Octavia Butler, and Margaret Atwood for understanding the patriarchal—or men-dominant—dynamics of the politics of pandemics in the twenty-first century. Like her literary followers in post-apocalyptic plague literature, Butler and Atwood, Shelley foresaw that the twenty-first century would be the age of lethal pandemics. Their post-apocalyptic fictions also projected the ways that patriarchal and authoritarian forms of populism could shape the cultural circumstances that can turn a local outbreak of a new and deadly contagious disease, like COVID-19, into a politically chaotic and economically devastating global plague. Modern feminist political science fiction born of Shelley's great pandemic novel The Last Man (1826) is seemingly clairvoyant not because of any supernatural powers of the authors but rather because of their studied attention to the wisdom of plague literature, the lessons of epidemic history, and the political dynamics of patriarchy and populism.